2013
DOI: 10.1093/mp/sst058
|View full text |Cite
|
Sign up to set email alerts
|

Heteromeric and Homomeric Geranyl Diphosphate Synthases from Catharanthus roseus and Their Role in Monoterpene Indole Alkaloid Biosynthesis

Abstract: Catharanthus roseus is the sole source of two most important monoterpene indole alkaloid (MIA) anti-cancer agents: vinblastine and vincristine. MIAs possess a terpene and an indole moiety derived from terpenoid and shikimate pathways, respectively. Geranyl diphosphate (GPP), the entry point to the formation of terpene moiety, is a product of the condensation of isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP) by GPP synthase (GPPS). Here, we report three genes encoding proteins with sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 69 publications
7
61
0
Order By: Relevance
“…This was in agreement with RNA in situ hybridization studies, which has shown the distribution of CrGES in internal phloem associated parenchyma (IPAP) cells of leaves, as well as carpels and stamens of flowers [14]. The gene encoding the small subunit of GPPS (GPPS.SSU), which was reported to regulate the formation of GPP in C. roseus, also exhibited higher expression in leaf, shoot and flowers [33] indicating co-regulation of GPP and geraniol production. MeJA is known to induce the expression of many genes of secondary metabolic pathways, including the genes of MIA biosynthesis leading to the accumulation of the corresponding metabolites such as alkaloids, terpenoids, flavonoids, and glucosinolates in different plant species [44].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This was in agreement with RNA in situ hybridization studies, which has shown the distribution of CrGES in internal phloem associated parenchyma (IPAP) cells of leaves, as well as carpels and stamens of flowers [14]. The gene encoding the small subunit of GPPS (GPPS.SSU), which was reported to regulate the formation of GPP in C. roseus, also exhibited higher expression in leaf, shoot and flowers [33] indicating co-regulation of GPP and geraniol production. MeJA is known to induce the expression of many genes of secondary metabolic pathways, including the genes of MIA biosynthesis leading to the accumulation of the corresponding metabolites such as alkaloids, terpenoids, flavonoids, and glucosinolates in different plant species [44].…”
Section: Discussionsupporting
confidence: 90%
“…MeJA is known to induce the expression of many genes of secondary metabolic pathways, including the genes of MIA biosynthesis leading to the accumulation of the corresponding metabolites such as alkaloids, terpenoids, flavonoids, and glucosinolates in different plant species [44]. In C. roseus, it has been previously reported that several MIA pathway genes such as GPPS, G8O, TDC, STR, D4H, DAT, and MIA pathway regulators like ORCA2, ORCA3 are induced in response to MeJA resulting in increased alkaloid accumulation [4,33,44,45]. Induction of CrGES in response to MeJA in leaf tissue (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers used for cloning into GFP vector are listed in Table S9. The fusion constructs were transformed into Arabidopsis protoplasts as described previously47. Transient expression of GFP fusion proteins was observed 16–20 h after transformation using confocal laser scanning microscope (Zeiss LSM 880) with a 40 × 1.55 numerical aperture lens.…”
Section: Methodsmentioning
confidence: 99%
“…RNA isolation, cDNA synthesis and qPCR analysis were performed as reported previously (Rai et al, 2013;Rastogi et al, 2014). For semi-quantitative RT-PCR, 18S rRNA gene served as an endogenous control for RNA quantity.…”
Section: Rna Isolation Cdna Synthesis and Qpcr Analysismentioning
confidence: 99%